2019
DOI: 10.1097/cm9.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medial meniscus extrusion on arthroscopic surgery outcome in the osteoarthritic knee associated with medial meniscus tear

Abstract: Background:The potential benefit of arthroscopic surgery for osteoarthritic knee associated with medial meniscus tear is controversial. This study was conducted to determine the effect of pre-operative medial meniscus extrusion (MME) on arthroscopic surgery outcomes in the osteoarthritic knee associated with medial meniscus tear during a minimum 4-year follow-up.Methods:This was a retrospective review of a total of 131 patients diagnosed with osteoarthritic knee associated with medial symptomatic degenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…However, arthroscopic debridement and osteotomies around the knee are also being employed in some instances in moderate knee OA before a TKR is required [ 51 , 52 ]. Wang et al [ 53 ], in a retrospective review of 131 patients who had undergone arthroscopic surgery for knee OA and were followed up for 4 years, found that in regard to pain relief, arthroscopic surgery was also beneficial in patients with major MME (> 3 mm). Goto et al [ 54 ] showed that varus alignment factors, and specifically medial proximal tibial angle (MPTA), were significantly related to the extent of MME, especially as the knee OA grade progressed.…”
Section: Knee Pathologies and Mementioning
confidence: 99%
“…However, arthroscopic debridement and osteotomies around the knee are also being employed in some instances in moderate knee OA before a TKR is required [ 51 , 52 ]. Wang et al [ 53 ], in a retrospective review of 131 patients who had undergone arthroscopic surgery for knee OA and were followed up for 4 years, found that in regard to pain relief, arthroscopic surgery was also beneficial in patients with major MME (> 3 mm). Goto et al [ 54 ] showed that varus alignment factors, and specifically medial proximal tibial angle (MPTA), were significantly related to the extent of MME, especially as the knee OA grade progressed.…”
Section: Knee Pathologies and Mementioning
confidence: 99%
“…Lerer et al [25] reported a high incidence of OA with meniscus extrusion, as high as 69%. Several studies have emphasized the pivotal role of MME in the progression of knee OA, both with and without clinical and radiographic features, making it a predictor of knee OA progression [8, 37–39, 42, 48].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, approximately 1.3 million KOA patients undergo TKR operations each year, and the operation rate is comparable to many European countries. In China, nearly 400,000 cases of TKR were reported in 2019, and the data is rising rapidly (Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%